Andrographolide attenuates LPS-stimulated up-regulation of C-C and C-X-C motif chemokines in rodent cortex and primary astrocytes - Wong, Siew Ying (J Neuroinflammation, 2016)
BACKGROUND: Andrographolide is the major bioactive compound isolated from Andrographis paniculata, a native South Asian herb used medicinally for its anti-inflammatory properties. In this study, we aimed to assess andrographolide’s potential utility as an anti-neuroinflammatory therapeutic. METHODS: The effects of andrographolide on lipopolysaccharide (LPS)-induced chemokine up-regulation both in mouse cortex and in cultured primary astrocytes were measured, including cytokine profiling, gene expression, and, in cultured astrocytes, activation of putative signaling regulators. RESULTS: Orally administered andrographolide significantly attenuated mouse cortical chemokine levels from the C-C and C-X-C subfamilies. Similarly, andrographolide abrogated a range of LPS-induced chemokines as well as tumor necrosis factor (TNF)-α in astrocytes. In astrocytes, the inhibitory actions of andrographolide on chemokine and TNF-α up-regulation appeared to be mediated by nuclear factor-κB (NF-κB) or c-Jun N-terminal kinase (JNK) activation. CONCLUSIONS: These results suggest that andrographolide may be useful as a therapeutic for neuroinflammatory diseases, especially those characterized by chemokine dysregulation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12974-016-0498-6) contains supplementary material, which is available to authorized users.